Emancipation through digital entrepreneurship: a critical realist analysis - Martinez Dy, Angela Carmina; Marlow, Susan; Martin, L. (SAGE, 2018)
Digital entrepreneurship is presented in popular discourse as a means to empowerment and greater economic participation for under-resourced and socially marginalised people. However, this emancipatory rhetoric relies on a flat ontology that does not sufficiently consider the enabling conditions needed for successful digital enterprise activity. To empirically illustrate this argument, we examine three paired cases of UK women digital entrepreneurs, operating in similar sectors but occupying contrasting social positionalities. The cases are comparatively analysed through an intersectional feminist lens using a critical realist methodological framework. By examining the relationships between digital entrepreneurship, social positionality, and structural and agential enabling conditions, we interrogate the notion of digital entrepreneurship as an emancipatory phenomenon producing liberated workers.